Advancing Gene Therapy: Next-Generation Viral Vector Engineering for Precision, Safety, and Scalability - Mehak Khanum; Jennifer S; Zaid Khan; Ehsan Mohebi (International Journal of Virus Studies, 2025)
Gene therapy has emerged as a paradigm-shifting modality for the treatment of genetic disorders, malignancies, and rare diseases through the delivery of therapeutic nucleic acids aimed at correcting or modulating dysfunctional gene expression. Among the various delivery systems, viral vectors including adeno-associated viruses (AAVs), lentiviruses, adenoviruses, retroviruses, and herpes simplex viruses have proven indispensable owing to their high transduction efficiencies and adaptability. This review offers a comprehensive assessment of viral vector optimization, tracing their historical development, identifying prevailing limitations, and highlighting recent advances in vector engineering. Critical barriers such as limited tissue specificity, immunogenic responses, cargo size restrictions, and challenges in large-scale production are systematically analyzed. Innovations in capsid engineering, the use of synthetic regulatory elements, and artificial intelligence (AI)-driven vector design are progressively mitigating these limitations, thereby enhancing vector safety, specificity, and therapeutic efficacy. Notable clinical successes, including Zolgensma for spinal muscular atrophy and Luxturna for inherited retinal dystrophies, underscore the clinical relevance of optimized vectors. The review also delineates a translational roadmap emphasizing the need for interdisciplinary collaboration, advanced biomanufacturing capabilities, and regulatory alignment to facilitate global accessibility and long-term clinical safety. Future perspectives include the integration of AI-assisted capsid design, CRISPR-based site-specific genome editing, and modular vector platforms to expedite the advancement of next-generation gene therapies.
Keywords: AI in gene delivery; Biomanufacturing; CRISPR integration; Capsid modification; Gene therapy; Immunogenicity; Vector engineering; Viral Vectors